2001
DOI: 10.2337/diabetes.50.3.660
|View full text |Cite
|
Sign up to set email alerts
|

Direct Regulatory Effect of Fatty Acids on Macrophage Lipoprotein Lipase

Abstract: Atherosclerosis is a major complication of type 2 diabetes. The pathogenesis of this complication is poorly understood, but it clearly involves production in the vascular wall of macrophage (Mo) lipoprotein lipase (LPL). Mo LPL is increased in human diabetes. Peripheral factors dysregulated in diabetes, including glucose and free fatty acids (FAs), may contribute to this alteration. We previously reported that high glucose stimulates LPL production in both J774 murine and human Mo. In the present study, we eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
2
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 65 publications
(33 reference statements)
4
46
2
1
Order By: Relevance
“…The regulation of Mo LPL in the arterial wall is poorly understood but may involve metabolic factors. This hypothesis is supported by our previous findings that Mo LPL is increased in patients with type 2 diabetes (30) and that metabolic factors dysregulated in diabetes, such as glucose (31) and fatty acids (32), enhance Mo LPL expression. On the basis of these findings and of the high levels of serum Hcys in patients with diabetes, we sought to evaluate the direct regulatory effect of Hcys on Mo LPL expression and to determine the molecular mechanism(s) involved in this effect.…”
supporting
confidence: 78%
“…The regulation of Mo LPL in the arterial wall is poorly understood but may involve metabolic factors. This hypothesis is supported by our previous findings that Mo LPL is increased in patients with type 2 diabetes (30) and that metabolic factors dysregulated in diabetes, such as glucose (31) and fatty acids (32), enhance Mo LPL expression. On the basis of these findings and of the high levels of serum Hcys in patients with diabetes, we sought to evaluate the direct regulatory effect of Hcys on Mo LPL expression and to determine the molecular mechanism(s) involved in this effect.…”
supporting
confidence: 78%
“…Although active in inhibiting apo C-III in rodents, the ability of PPAR-␣ agonists to lower apo C-III in humans remains controversial (38,50). PPAR-␣ agonists may also decrease TG levels by increasing the expression of LPL in the liver (77) and in macrophages (2,60). How much of the hypotriglyceridemic effect of PPAR-␣ ligands can be ascribed to direct versus indirect effects (via decreased apo C-III) on LPL is not yet known.…”
Section: Ppar-␣ Effects On Tg Ldl and Hdl Metabolismmentioning
confidence: 99%
“…The heart also expresses LPL, which has been found to be upregulated in the liver and macrophages in response to PPAR-␣ agonists (60,77). Although likely a key player in myocardial TG hydrolysis and fatty acid uptake, cardiac LPL activity has been found to be inhibited by PPAR-␣ agonists in cultured rat cardiomyocytes (12).…”
Section: Ppar-␣ and The Heartmentioning
confidence: 99%
“…14 This activation occurs by the binding of PPARg and the 9-cis retinoic acid receptor (RXR) heterodimers to the PPAR response element (PPRE) sequence (À169 TGCCCTTTCC CCC À157) in the promoter of the LPL gene. 15,16 Important cis-acting elements in the promoter of LPL gene have been identified that bind DNA-binding proteins and appear to confer basal and/or ligand-mediated LPL gene transcription. 17 DNA variants in the promoter of the LPL gene have been shown to be associated with changes in lipid metabolism leading to type 2 diabetes and its related traits.…”
Section: Introductionmentioning
confidence: 99%